Pengaruh Pemberian Insentif Perjalanan Wisata terhadap Motivasi dan Kinerja Agen Asuransi: Studi pada PT. AXA Financial Indonesia Sales Office Cabang Solo - Aracelli Evalia; Miko Andi Wardana; I Wayan Eka Sudarmawan (Universitas Pendidikan Ganesha, 2022)
Providing travel incentives as a form of appreciation is one of many ways used by companies to boost their employee’s motivation that could be resulting in a better performance. This research aims to identify the significant influence of travel incentive towards employee performance; influence of travel incentive towards work motivation; influence of work motivation towards employee performance; and to explain the mediating role of employee motivation between travel incentives and employee performance. The data provided for this research is collected through questionnaires and document study, whilst the analysis technique for this quantitative research is using statistic descriptive and inferential analysis using SmartPLS3. Samples of this research are the insurance agent of AXA Financial Indonesia (AFI) Ltd. Surakarta Branch. The result of this research shows that there is no direct influence between travel incentive towards employee performance. However, travel incentive has strong significance influence towards work motivation and work motivation has significance influence towards employee performance. With t-statistics of travel incentive towards work motivation is 12,231 whilst t-statistics of work motivation towards employee performance is 6,497. Moreover, work motivation has a role as partial mediator between travel incentive and employee performance with a Variance Accounted For (VAF) value of 0,78 .